1994
DOI: 10.1016/0378-1097(94)90025-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect on enterotoxicity of protease purified from Vibrio cholerae O1

Abstract: The effect on enterotoxicity of protease purified from Vibrio cholerae O1 was investigated by the inoculation of live vibrio cells into protease-treated loops of the ileal loop model. Fluid accumulation ratios in the protease-treated loops were elevated in a dose-dependent manner by challenge with live vibrio cells but not by that with toxin. An enhancement effect of protease on enterotoxicity was observed in both serotypes of V. cholerae O1 and V. cholerae non-O1. It is suggested, therefore, that the enteroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…5A). Our results are in agreement with the finding that pretreatment of ileal loops with purified V. cholerae HapA increased fluid accumulation in loops inoculated with live vibrios (20). The hapA and hapA motY mutants expressed less CT and TcpA (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…5A). Our results are in agreement with the finding that pretreatment of ileal loops with purified V. cholerae HapA increased fluid accumulation in loops inoculated with live vibrios (20). The hapA and hapA motY mutants expressed less CT and TcpA (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…It also nicks and activates CT and CT-related enterotoxins [24]. Besides the protease activity, HA/P also shows hemagglutinating activity [25,26] on erythrocytes of Balb/c mice, but this activity has not been consistently reproduced [27,28]. Our study showed that NMDCY has a protease activity which is inhibited by metal chelators, but has no hemagglutinating activity on Balb/c mice and chicken erythrocytes.…”
Section: Resultsmentioning
confidence: 97%
“…The RIL test was carried out using Japanese white rabbits weighing 2.0-2.5 kg by the method of Ichinose et al (13). Briefly, rabbits starved for 48 hr were anesthetized with sodium pentobarbital (20 mg kg-1 of body weight) and laparotomy was performed.…”
Section: Methodsmentioning
confidence: 99%